2020
DOI: 10.1021/acsomega.9b04020
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanoparticles on Sintered Metal Fibers Are Efficient Structured Catalysts in Partial Methane Oxidation into Synthesis Gas

Abstract: Efficient structured catalysts of partial methane oxidation into synthesis gas were obtained by electrochemical modification of the surface of sintered FeCrAl alloy fibers in an ionic liquid BMIM-NTf 2 with further introduction of platinum nanoparticles. It was shown that etching and electrochemical modification of sintered FeCrAl alloy fibers result in a decrease of the surface aluminum content. With an increase of the reaction temperature to 900 °C, the methane conversion reaches 90% and the selectivity to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Interestingly, the addition of acetonitrile to the electrolyte leads to a decrease in the particle size from 3 nm to 1 nm. The electrodeposition of nickel, cobalt and their alloys with aluminum on the surface of Au (111) was also studied in an earlier work [89].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the addition of acetonitrile to the electrolyte leads to a decrease in the particle size from 3 nm to 1 nm. The electrodeposition of nickel, cobalt and their alloys with aluminum on the surface of Au (111) was also studied in an earlier work [89].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
“…The distortion of the hexagonal structure is apparently caused by the shielding of the electric field due to the fibrous structure of steel. Fibers with such a surface structure were applied as substrates of effective catalysts for the partial oxidation of methane [111]. Sun et al reported the synthesis of nanoporous structures based on metals (Au, Pt, Ag) by electrodeposition of binary alloys (Au-Zn, Pt-Zn, Ag-Zn) followed by electrochemical removal of one of the alloy components, i.e., zinc (dealloying), using a mixture of zinc chloride and EMIMCl [112][113][114].…”
Section: Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various experimental studies have investigated the effects of rare earth elements on oxidation behavior [ 23 , 24 , 25 , 26 , 27 , 28 ]. However, the literature survey reveals few technical papers on FeCrAl fibers [ 17 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Li et al [ 31 ] and Fornasiero et al [ 32 ] investigated FeCrAl fibers as a substrate and support of catalysts.…”
Section: Introductionmentioning
confidence: 99%